Improving the Effectiveness of the Healthy, Natural, and Economical (SAE) Hunting Program in Margasari Village, Buah Batu District, Bandung City - Sumiati, Imas; Martiawan, Rudi; Salamah, Dedeh Siti; Fadillah, Mella Nur (Pascasarjana Universitas Mataram, 2025)
The Buruan SAE program is a program by the Bandung City Government through the Bandung City Food Security and Agriculture Office, which is unique in that it utilizes home gardens or idle land for planting. By utilizing home garden land, the Buruan SAE activity becomes a suitable innovation for addressing food issues. In its implementation, the effectiveness of the SAE Hunting Program in RW 10, Margasari Village, Buah Batu District, is not yet optimal, and there are several obstacles, such as limited land and the need to overcome technical support to optimize the program's results. The solutions offered are continuous education and socialization, continuous monitoring and evaluation, and optimizing the use of existing land.